Literasi Keuangan Dan Tingkat Beban Utang Pada Generasi Milenial Di Bengkulu - Oktafian Histori S (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to examine the level of financial literacy and its relationship with the level of one's debt burden in the millennial generation in Bengkulu. The methodology of this research was carried out with qualitative methods with technical data collection through semi-structured interviews. The findings of this study indicate that the millennial generation in Bengkulu has a fairly good level of financial literacy, which is 42% and there is a significant relationship between the level of financial literacy and the level of their debt burden. In addition, the largest composition of the debt burden among the millennial generation is multipurpose loans, followed by housing loans, motor vehicle loans and other household loans. The main problem with the level of debt burden is the lack of financial management and financial skills of respondents. Keywords: Financial Literacy, Debt Burden, Millennials